The Effect of Building Block Game to the Ability of Social Interaction of Child with Autism Grade II - Aini, Tri Nur (Indonesian Journal of Disability Studies, 2019)
The aim of this research is to know the effect of building block game to the ability of social interaction of the child with autism grade II in SD Al Firdaus Surakarta in the year of 2018/2019. The research was using an experimental approach single subject or known as single-subject research (SSR) with A-B-A design. The result of the analysis showed the tendency of the direction and change of the level increased +1 at baseline-1 (A1), increased +4 at intervention (B), and constant =0 at baseline-2 (A2). High stability trend and overlap percentage of 0%. In baseline-1, the average score was 14,67 points; on intervention, the average score was increasing into 24,85 points; then on baseline-2, the average score was increasing again into 27 points. Based on the above result it can be concluded that the building block game has a positive effect on the ability of social interaction of the child with autism in second grade at SD Al Firdaus Surakarta in the year of 2018/2019.